Integrative mRNA and Long Noncoding RNA Analysis Reveals the Regulatory Network of Floral Bud Induction in Longan (Dimocarpus longan Lour.) - Liang, Fan; Zhang, Yiyong; Wang, Xiaodan; Yang, Shuo; Fang, Ting; Zheng, Shaoquan; Zeng, Lihui (Frontiers in Plant Science, 2022)
Flowering is an essential process for the yield in fruit trees. Due to the instability of flowering, it is necessary to understand the molecular mechanisms of floral induction in longan (Dimocarpus longan Lour.), which is a tropical/subtropical fruit tree of significant economic importance. In this study, mRNA and long noncoding RNA (lncRNA) transcriptome sequencing were performed using the apical buds of parent branches as the materials. A total of 7,221 DEmRNAs and 3,238 DElncRNAs were identified, respectively. KEGG enrichment analysis of DEmRNAs highlighted the importance of starch and sucrose metabolic, circadian rhythms, and plant hormone signal transduction pathways during floral induction. Combining the analysis of weighted gene co-expression network (WGCNA) and expression pattern of DEmRNAs in the three pathways, specific transcriptional characteristics at each stage during floral induction and regulatory network involving co-expressed genes were investigated. The results showed that sucrose metabolism and auxin signal transduction may be crucial for the growth and maturity of autumn shoots in September and October (B1-B2 stage); starch and sucrose metabolic, circadian rhythms and plant hormone signal transduction pathways participated in the regulation of floral bud physiological differentiation together in November and December (B3-B4 stage) and the crosstalk among three pathways was also founded. Hub genes in the co-expression network and key DEmRNAs in three pathways were identified. The circadian rhythm genes FKF1 and GI were found to activate SOC1gene through the photoperiod core factor COL genes, and they were co-expressed with auxin, gibberellin, abscisic acid, ethylene signaling genes and sucrose biosynthesis genes at B4 stage. 12 hub-DElncRNAs had potential for positively affecting their distant genes in three putative key pathways, predominantly in a co-transcriptional manner. A hypothetical model of regulatory pathways and key genes and lncRNAs during floral bud induction in longan was proposed finally. Our studies will provide valuable clues and information to help elucidate the potential molecular mechanisms of flower initiation in longan and woody fruit trees.